ASSESSMENT OF LONG-TERM ORGANIC AMENDMENTS EFFECT ON SOME SENSITIVE INDICATORS OF CARBON UNDER SUBTROPICAL CLIMATIC CONDITION - RAJEEV PADBHUSHAN; RAJIV RAKSHIT; ANUPAM DAS; RAJENDRA PRASAD SHARMA (The Bioscan, 2015)
The present study deals with the effect of long-term organic amendments on some sensitive indicators of soil carbon pools. Organic manures addition increased the amount of labile carbon (Cl) by 54.5-77.3 % as compared to chemical fertilizer applied alone in soil depth 0-10 cm. The amount of carbon pools decreased on increasing soil depth (0-10 cm> 10-20 cm> 20-30 cm). In the soil depth 0-10 cm, carbon management index (CMI) values were 1.80-1.62 times more in organic manure added treatments as compared to chemical fertilizer applied alone. Sensitivity index (SI) of labile carbon for different treatments showed positive values, which indicates positive impact of the management practices on soil organic matter content and on the soil quality. The management practices are approaching towards natural ecosystem.